2011
DOI: 10.1097/acm.0b013e31821db1bc
|View full text |Cite
|
Sign up to set email alerts
|

Teachers as Learners: The Effect of Bedside Teaching on the Clinical Skills of Clinician–Teachers

Abstract: Teachers perceived profound positive impact on their clinical skills from teaching preclerkship students at the bedside. Further studies are needed, including comparing teaching preclerkship students with teaching advanced students and residents, to assess whether teaching at other levels has this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 16 publications
1
27
0
2
Order By: Relevance
“…They also noted improved confidence in their clinical examination skills. This supports the earlier work of Wenrich et al [13], who noted that bedside teaching was perceived to have a profoundly positive impact on the clinical skills of near-peer teachers. In an objective study of MSK PE skills, Button et al [14] reported significantly improved practical MSK PE scores for PM&R residents who participated as teachers in a near-peer teaching model; this effect did not occur for residents who simply attended the sessions without participating in any teaching activities.…”
Section: Discussionsupporting
confidence: 89%
“…They also noted improved confidence in their clinical examination skills. This supports the earlier work of Wenrich et al [13], who noted that bedside teaching was perceived to have a profoundly positive impact on the clinical skills of near-peer teachers. In an objective study of MSK PE skills, Button et al [14] reported significantly improved practical MSK PE scores for PM&R residents who participated as teachers in a near-peer teaching model; this effect did not occur for residents who simply attended the sessions without participating in any teaching activities.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, evidence has shown that the examination skills of medical students and clinicians have deteriorated (Mangione and Peitzman, ; Wenrich et al, ; Oliver et al, ). This is, in part, attributed to a greater reliance on improving imaging technologies and other investigation modalities to diagnose patients, (Dunnington et al, ; Macdessi and Oates, ; Bordage, ; Mangione and Peitzman, ; Tavel, ; Anderson et al, ; Fagan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Only by spending more time at the bedside can teachers improve their bedside teaching skills. 26 Residency programs need to design innovative curricula to improve clinical skills of trainees where residents' historytaking and physical examination skills are observed, clinical reasoning is probed, residents are required to justify diagnostic and management approaches, and clinical skills are assessed before graduation. High-touch and high-tech medicine can be successfully combined by developing a cadre of master clinicians to champion and spearhead ''back to bedside'' initiatives and by having all clinical teachers serve as bedside role models.…”
Section: Casementioning
confidence: 99%